O ideb de duas escolas públicas de Araguaína: uma análise dos projetos políticos pedagógicos. - Lopes, Tamires Rocha (Universidade Federal do Tocantins, 2022)
This work brings out the analysis and questioning the reality of the Basic Education Development Index (IDEB) in two public schools in Araguaína, considering the indication and the discursive merger that are under the Projeto Politico Pedagógico (PPP). Assuming that the PPP is configured as a relevant document and established by law, especially the idea that they create a reality and an identity for the school institution, it is necessary to carry out this work, as it shows the way as schools, from the performance of its professionals, they give a place to the national policy of IDEB. This policy makes up the size of the school curriculum. Therefore, we sought to show how each school scales this policy and what kind of relationship is presented in this dimension, with the PPP as a starting point. Therefore, we prepared some questions such as: what is the role of PPP in the document condition that creates a reality for the school? As mentioned in the IDEB PPP? What intervention actions and confrontation of reading questions? In that sense the IDEB influence on the specifics of the practices of school management? The analysis will show that the reality of IDEB is constant within the PPP of the two schools, and the issue of school performance of students is outlined, emphatically, with the IDEB numbers as the horizon. The strategic actions outlined by the school take these figures into account, leaving trigger a relationship that, in this work, we will call monolithically. It is a relationship that is marked by way of limitation, not having, in many instances a criticality.